2005
DOI: 10.4103/0378-6323.16232
|View full text |Cite
|
Sign up to set email alerts
|

A study of serum nitric oxide levels in psoriasis

Abstract: Nitric oxide levels were significantly increased in patients with psoriasis and these levels showed a positive correlation with severity and duration in the chronic plaque type group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 11 publications
5
22
0
6
Order By: Relevance
“…Our results demonstrating significantly increased NO levels in plasma of active psoriatic patients seem to be in agreement with literature data [9,10]. Decreasing but still significantly higher NO plasma levels after 3 weeks of effective treatment suggest that the balance in NO metabolism has not been restored yet.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Our results demonstrating significantly increased NO levels in plasma of active psoriatic patients seem to be in agreement with literature data [9,10]. Decreasing but still significantly higher NO plasma levels after 3 weeks of effective treatment suggest that the balance in NO metabolism has not been restored yet.…”
supporting
confidence: 93%
“…Gokhale et al [9] demonstrated significantly increased mean serum NO level in 36 patients presenting different types of psoriasis (chronic, erythrodermic, pustular) and found significantly higher NO levels in patients with active disease as compared to normal individuals. Örem et al [10] observed low NO serum levels during the inactive phase in psoriatic patients (mean PASI 1.7).…”
mentioning
confidence: 97%
“…Some authors have reported improvement of the Ps plaque with the topical application of NO-donors [1] while others found the opposite effect [23]. Significantly increased nitrite/nitrate levels were found in plasma of patients with Ps and, furthermore, these levels showed a positive correlation with PASI score [9].…”
Section: Discussionmentioning
confidence: 97%
“…A few studies also determined the levels of nitrite and nitrate (two NO metabolites) in blood samples of Ps patients [9,24,28]. Nitrite/nitrate levels were significantly increased in plasma of Ps patients compared to healthy control and showed a positive correlation with PASI score [9], and a significant reduction of the metabolite levels after treatment with metothrexate has also been reported [28].…”
Section: Introductionmentioning
confidence: 97%
“…It was reported that levels were significantly higher in the patients group. Moreover, in the chronic plaque group NO levels increased with the duration of the disease [51]. Serum levels of NO in normal controls, psoriatic patients prior to, and after treatment with methotrexate were compared.…”
Section: Innate Immune Response a Cells And Their Receptors 1 Rementioning
confidence: 99%